Effectiveness and safety of eberconazole 1% cream in Indian patients with Tinea corporis and Tinea cruris: a prospective real-world study - Thomas, Jayakar; Das, Siddhartha; Ghate, Sunil; Chatterjee, Manas; Teltumde, Sharad; Charugulla, Sujeet Narayan; Mehta, Suyog; Mane, Amey; Rathod, Rahul; Kale, Ravindra (International Journal of Research in Dermatology, 2020)
Background: Tinea corporis and cruris are estimated to affect 22% to 55% of the Indian population. This real-world study was conducted to evaluate the effectiveness and safety of eberconazole 1% cream among Indian patients. Methods: In this prospective, single-arm, observational study, patients with Tinea corporis and cruris aged ≥18 years were prescribed eberconazole 1% cream (Ebernet®, Dr. Reddy’s Laboratory, India) for up to 3 weeks. The primary endpoint was proportion of patients with improvement in total signs and symptoms score with 2 weeks of treatment. The key secondary endpoint was mean percent reduction in individual signs and symptoms score (erythema, itching, scaling) from baseline to the end of the 1st, 2nd, and 3rd week. A post-hoc analysis was performed on a subgroup of patients (completer set [CS]) who reported application of eberconazole 1% cream for 3 weeks in the study. There were no adverse effects reported. Results: Of 120 enrolled patients;104 (86.7%) were included in the full analysis set (FAS) and 76 (63.3%) patients were included in the CS. After 2 weeks of treatment, total signs and symptoms score<2 was achieved by 25% of patients in the FAS and 28.9% in the CS. After 3 weeks of treatment, mean percent reduction in total sign and symptom score was 60.3% for erythema, 61.2% for itching, and 76.8% for scaling. Conclusions: The evidence from this real-world observational study and a post-hoc analysis suggests that eberconazole 1% cream is effective and safe treatment option in the management of Tinea corporis and cruris in Indian patients.